2021
DOI: 10.3390/coatings11111361
|View full text |Cite
|
Sign up to set email alerts
|

Condition Assessment of Solar Modules by Flash Test and Electroluminescence Test

Abstract: The Hungarian society and the Hungarian state are constantly increasing their solar capacity. More and more solar power plants are being put into operation. The largest of these has a 100 MW peak capacity. Such power plants do not require constant maintenance. However, in the case of low productivity, a conditional assessment is required. The reason for production loss can also be manufacturing, installation, and operational errors. A flying drone was used for finding failures by thermographic scouting. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In less than five years since its handover, it has been continuously observed that the performance of solar panels is greatly reduced. Based on the results of the electrical measurements, it was found that a solar panel numbering in the order of hundreds failed [2]. Defective solar panels have been detected using flying drone [4] and replaced after that.…”
Section: Presentation Of the Power Plant And The Surface Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…In less than five years since its handover, it has been continuously observed that the performance of solar panels is greatly reduced. Based on the results of the electrical measurements, it was found that a solar panel numbering in the order of hundreds failed [2]. Defective solar panels have been detected using flying drone [4] and replaced after that.…”
Section: Presentation Of the Power Plant And The Surface Contaminationmentioning
confidence: 99%
“…Some contaminants have thermal-insulation properties; hence, the heat generated on the contaminated cells cannot be transferred to the environment. The temperature of shaded, contaminated cells can be up to 40-50 • C higher than that of clean cells, which can cause fire accidents [1,2]. This research examined the concentration at which each pollutant can cause a temperature rise and the extent to which the lifespan of permanently polluted panels decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, emphasis is placed on the analysis of recent literature reviews [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. In addition, the literature is complemented with standards [69][70][71], selected papers [72][73][74][75][76], and reports [77].…”
Section: Photovoltaic (Pv) Systemsmentioning
confidence: 99%
“…Other investigations use infrared thermography to detect hot spots in PV systems [56,62,64,69]. Moreover, flash, electroluminescence, and X-ray tests are employed to find defects in PV arrays [59,60,72]. It is worth noting that the I-V characteristic can be analyzed indirectly using thermography, flash, electroluminescence, and X-ray because there is a relation between hot spots and defects found with those tests and the voltage and current performance of the PV system.…”
Section: Fault Diagnosis and Condition Assessment Of Pv Systemsmentioning
confidence: 99%